Revamping the design of Preschoolers Islamic Education by Integrating Islamic Design Principles and Cognitive Theory of Multimedia Learning: A Needs Assessment Study (Sains Humanika, 2019)
This study aims at identifying the needs in applying Islamic Design Principles in developing multimedia learning for Islamic Education among children. Teaching methods of Islamic education have not seen much improvement and lack of creativity. Current designs and content of multimedia learning materials were not suitable in teaching Islamic education. Thus this study initiated in integrating Islamic design principles; 1) Tawheed, 2) Dhikir 3) Haya and 4) Iqtisad with Cognitive Multimedia Learning Theory.Â  It involved a needs analysis survey research design concerning parents and teachers of preschool as participants. The result of this study indicated positive responses received upon this matter indicating that the elements of Islamic design principles were relevant in multimedia learning for preschool Islamic Education. The integration of multimedia learning theory and Islamic Design Principles in designing multimedia learning for children. This was because the impacts of multimedia learning and Islamic design principles were important for the future of early children education, it was sensible for Islamic design principles were applied to multimedia learning content. There was a need to develop learning aids in teaching Islamic values education to the children. Multimedia learning can help in sculpting the Islamic character of the children while coaching them the virtuous values in Islam; an example of the ethic in Prophet Muhammad (P.B.U.H.), good behavior and action will help the children in their personal life. Besides, this paper will help instructional design to design and develop a multimedia learning for Islamic preschool in future.
Keywords: Islamic design Principles; Multimedia learning theory; preschoolers; instructional technique